2024
DOI: 10.1039/d4ra00852a
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of amorphous anodized TiO2 nanotube arrays

Zhiqiang Wang,
Kunfeng Chen,
Dongfeng Xue

Abstract: Amorphous anodized TiO2 nanotube arrays show amorphous-to-anatase transition. The amorphous–anatase mixed structure significantly improved Li-ion battery performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…36 The BET method was utilized to calculate the SSA, as described in eq 9. 32 = × D SSA 6 10 3 p (9) where ρ the density of the material and D p denotes the crystal size. With an increase of calcination temperature, the crystallite size of the NPs increases.…”
Section: Acs Appliedmentioning
confidence: 99%
See 3 more Smart Citations
“…36 The BET method was utilized to calculate the SSA, as described in eq 9. 32 = × D SSA 6 10 3 p (9) where ρ the density of the material and D p denotes the crystal size. With an increase of calcination temperature, the crystallite size of the NPs increases.…”
Section: Acs Appliedmentioning
confidence: 99%
“…Furthermore, such studies can guide the synthesis of materials with improved thermal stability and performance, addressing specific needs in high-temperature environments. 9 This study delves into the impact of different calcination temperatures on the optical properties, phase transitions, and morphologies of TiO 2 NPs and BN-TNTs. While different calcination temperatures for TiO 2 NPs have been reported in the literature, corresponding studies for BN-TNTs have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations